2011
DOI: 10.1007/s00595-011-0019-2
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic repair of an incarcerated groin hernia with small intestinal resection

Abstract: Strangulated inguinal hernias cannot be considered a contraindication to the use of a prosthetic mesh even in cases requiring small-intestinal resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…These initial data were confirmed recently showing similar infection rates but reduced recurrence rates in the long-term follow-up in the mesh group [11][12][13][14]. These results have been reproduced even in the context of concomitant bowel resection [15,16]. So far, no consensus has been reached on mesh placement for the treatment of incarcerated hernias.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…These initial data were confirmed recently showing similar infection rates but reduced recurrence rates in the long-term follow-up in the mesh group [11][12][13][14]. These results have been reproduced even in the context of concomitant bowel resection [15,16]. So far, no consensus has been reached on mesh placement for the treatment of incarcerated hernias.…”
Section: Introductionmentioning
confidence: 69%
“…However, colorectal procedures are associated with high SSI rates between 5.2 and 8.9 % [29]. Of note, Ueda et al [16] reported 20 % SSI in their overall population with no 27]. Several studies conclude that the use of mesh does not increase the risk for complication in the absence of bowel resection [4,11,27,[30][31][32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the use of a mesh for the tension-free repair of an emergency hernia does not seem to be an absolute contraindication 11 . A mesh is safe to apply even in cases of intestinal resection and anastomosis 10,[17][18][19][20] . Evidence has accumulated regarding the application of synthetic meshes, and clinicians recommend the use of synthetic meshes to repair FHs in patients, including in emergency situations 2,10,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Some may argue that in case of strangulated hernia requiring bowel resection, the use of mesh for repair was contraindicated due to the risk of mesh infection. But recent studies had showed that bowel resection was not related to postoperative mesh infection nor wound infection [5]. Recent further advancement of laparoscopic surgery with single port instrument allowed further reduction of invasiveness of laparoscopic hernia repair.…”
Section: Discussionmentioning
confidence: 99%